2004
DOI: 10.1016/s0749-8063(04)00590-0
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic autogenous osteochondral transplantation for treating knee cartilage defects: A 2- to 5-year follow-up study

Abstract: Level IV, therapeutic, case series (no, or historical, control group).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(64 citation statements)
references
References 0 publications
2
60
0
2
Order By: Relevance
“…Chow et al [20], in their study of 30 knees, performed second-look arthroscopy in eight patients without symptoms and found a correlation between the clinical result and second-look arthroscopy. Marcacci et al [15] did second-look arthroscopy in five patients which showed good coverage and integration at the short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chow et al [20], in their study of 30 knees, performed second-look arthroscopy in eight patients without symptoms and found a correlation between the clinical result and second-look arthroscopy. Marcacci et al [15] did second-look arthroscopy in five patients which showed good coverage and integration at the short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Kish et al [13] treated 52 athletes with the same technique and after a minimum one year follow-up stated that 63% of the patients had returned to full sport participation. Chow et al [20], in a study with 30 patients, carried out arthroscopic mosaicplasty for osteochondral lesions sized 1-2.5 cm 2 and with a minimum two year follow-up found 83.3% excellent and good outcome. Marcacci et al [15], in a study of 37 patients, concluded that mosaicplasty was a safe and satisfactory technique at the short-and medium-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autologous osteochondral transplantation gained popularity for the treatment of articular cartilage injuries following successful experiments and clinical results [2,5,11,18]. Our study suggests that FGF-2 accelerates the integration of the graft and the host in articular cartilage defects in an animal model.…”
Section: Discussionmentioning
confidence: 61%